Remoción de colorantes asociados a residuos de tinción de gram utilizando arcillas gelificadas en alginato de sodio (2021)
The world is going through an unprecedented environmental crisis due to the contamination of renewable and non-renewable natural resources due to the mismanagement of human beings. Small and large-scale industrial processes produce innumerable wastes that, without proper treatment, can affect water sources. The dye residues associated with Gram staining generate high contamination of water resources which greatly affects the health of animals and humans due to its harmful and toxic effect, so the main objective of this work is carry out a bibliographic search on the history and current status of the removal of dyes associated with Gram stain residues using gelled clays in sodium alginate and the current contamination to which Colombia is subjected.